External match load and the influence of contextual factors in elite futsal - Spyrou, K.; Freitas, T. T.; Marín-Cascales, E.; Herrero-Carrasco, R.; Alcaraz, P. E. (Biology of Sport, 2022)
Quantifying external load during futsal competition can provide objective data for the management of the athlete`s performance and late-stage rehabilitation. This study aimed to report the match external load collected via wearable technology according to time periods (i.e., halves) and contextual factors (i.e., team`s ranking, match result, and location) in elite futsal. Nine professional male players used a GPS-accelerometer unit during all games of the 2019-2020 season. Player load (PL), PL·min-1, high-intensity acceleration (ACCHI), deceleration (DECHI), explosive movements (EXPL-MOV), and change of direction (CODHI) data were collected. On average, players displayed values of: total PL 3868 ± 594 a.u; PL·min-1: 10.8 ± 0.8 a.u; number of ACCHI: 73.3 ± 13.8, DECHI: 68.6 ± 18.8, EXPL-MOV: 1165 ± 188 and CODHI: 173 ± 29.1. A moderate and significant decrease was found in the 2nd half for total PL (p = 0.03; ES = 0.52), PL·min-1 (p = 0.001; ES = 1.16), DECHI (p = 0.001; ES = 0.83), and EXPL-MOV (p = 0.017; ES = 0.58) compared to the 1st half. Small and non significant differences were found between contextual factors. In summary, this study indicates that futsal players are exposed to high-intensity mechanical external loads, and perform a great number of ACCHI, DECHI, EXPL-MOV and CODHI, without being influenced by the team ranking, result and match location. Coaches and sports scientists are advised to implement speed-power, DEC, and COD activities in the training sessions, and may use these reference values to design specific training and return-to-play plans.